Enhanced Glyphosate Degradation Using Laccase-Immobilized Magnetic Iron Oxide Nanoparticles: A Comparative Study - Amanpreet K. Sidhu; Sucheta N. Patil; Vishwasrao B. Gaikwad (Journal of Water and Environmental Nanotechnology)
Glyphosate, a widely used herbicide, poses environmental concerns due to its persistence and potential health hazards. In this study, we explored the efficacy of the laccase enzyme immobilized on the surface of magnetic iron oxide nanoparticles (IONPs) for the degradation of glyphosate pesticides. The immobilized laccase exhibited facile recovery and reusability, offering a sustainable approach to pesticide remediation. A comparative investigation was conducted to assess the degradation efficiency of glyphosate using free laccase enzyme and two variants of laccase immobilized on IONPs, namely IONP-Thio-Lac and IONP-PVA-Lac. Optimization experiments were conducted to evaluate the impact of pesticide concentration, temperature, incubation time, and enzyme units on the degradation process. High-Performance Liquid Chromatography (HPLC) studies confirmed the efficacy of the immobilized laccase systems. Results revealed that after 1 hour, the percent degradation of a 5000 ppm glyphosate solution using free laccase, IONP-Thio-Lac, and IONP-PVA-Lac were 29.534%, 40.533%, and 74.758%, respectively. The findings underscore the effectiveness of laccase immobilization on magnetic nanoparticles for glyphosate degradation, with IONP-PVA-Lac exhibiting the highest degradation efficiency. This research highlights a promising strategy for sustainable pesticide remediation, offering potential applications in environmental protection and agriculture.